2016
DOI: 10.1371/journal.pone.0155051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Iron Deficiency Anemia in Children under Five Years of Age in Pakistan, A Secondary Analysis of National Nutrition Survey Data 2011–2012

Abstract: BackgroundIron deficiency Anemia (IDA) in children is a recognized public health problem that impacts adversely on child morbidity, mortality and impairs cognitive development. In Pakistan information on the true prevalence and predictors of IDA is limited. This study sought to investigate IDA in children under five years of age using data from a nationally representative stratified cross-sectional survey.MethodsSecondary analysis was performed on the National Nutrition Survey in Pakistan 2011–2012. We used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
78
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 44 publications
18
78
4
Order By: Relevance
“…A study by Killip et al showed that, in Pakistan among children from 6 months to five years of age, 62.3% were anemic (hemoglobin levels <110 g/L), while 33.2% had iron deficiency anemia (defined as having both hemoglobin levels <110 g/L and ferritin levels <12  μ g/L). Ferritin deficiency (ferritin levels <12  μ g/L) was present in 47.1% cases, and 13.9% had ferritin deficiency without anemia [10, 11]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Killip et al showed that, in Pakistan among children from 6 months to five years of age, 62.3% were anemic (hemoglobin levels <110 g/L), while 33.2% had iron deficiency anemia (defined as having both hemoglobin levels <110 g/L and ferritin levels <12  μ g/L). Ferritin deficiency (ferritin levels <12  μ g/L) was present in 47.1% cases, and 13.9% had ferritin deficiency without anemia [10, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis, conducted among children from 6 months to 59 months of age, showed that anemia was associated with both underweight and stunting in majority of the studies [19]. Secondary analysis was performed on the National Nutrition Survey in Pakistan 2011-2012 conducted by Killip et al which showed that stunting was associated with iron deficiency anemia among the children from 6 months to 5 years of age [10, 11]. Regression model of our study showed that ferritin level was not predictable by status of height and weight, gender, age, and presence of anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is an emerging health related concern in Pakistan and so are ID and IDA [1820]. It is also worth mentioning that serum ferritin assay is the most commonly used blood test to diagnose ID or IDA, not only in Pakistan, but in other developing countries of the world also.…”
Section: Introductionmentioning
confidence: 99%
“…The youngest are the worst affected as a study shows that iron deficiency is most prevalent in areas of poor access where mothers are also deficient 4. It is imperative to address anemia in mothers to prevent its occurrence in children.…”
Section: Introductionmentioning
confidence: 99%